DESCRIPTIONS OF STUDENTS’ UNDERSTANDINGS ON POWERS OF NUMBERS AND ROOT FORMS IN GRADE X OF MADRASAH ALIYAH PESANTREN AN-NAHDLAH LAYANG MAKASSAR - Mukarramah Mukarramah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This study aims to describe the students’ instrumental and relational understanding about the form of Powers of Numbers and root in grade X of Madrasah Aliyah Pesantren An-Nahdlah Layang Makassar. The type of research used is descriptive qualitative explorative research. Subjects in this study were six students of grade X Academic Year 2016/2017 which were divided into three groups (advance, intermediate, and low levels) selected based on initial ability test results. The data collected consisted of preliminary test result data, mathematics comprehension test data and interview result data. Data were analyzed using qualitative descriptive analysis. Description of research results are divided into two parts, namely instrumental understanding and relational understanding. Description of the instrumental understanding of the three groups is to explain the concept only procedurally based on what the subject memorized, experiencing misconceptions about the concept of the root form, solving the question of form Powers of Numbers by using one way when there are other alternatives that can be used in solving the problem, and applying the concept of Powers of Numbers to the problem solution, experiencing misconceptions about the concept of the root form. The relational understanding of the three groups was different. Higher subject groups presented examples and not examples of more than one form of Powers of Numbers, presented the concept of Powers of Numbers to another mathematical representation with the reason and presentation of more than one, utilize the concept of Powers of Numbers in solving the problem relating to the concept, and solvde the question which deals with the form of a fractional Powers of Numbers with more than one way accompanied by reason. While the intermediate subject group was to understanding how to present the concept of the form of fractional form to the root form and vice versa and understand how to apply the writing of scientific notation to problem solving. Relational understanding of low subject groups was not found in the study